Neighbor discovery-based security enhancement using threshold cryptography for IP address assigning in network - Santhosh Kumar, R; Bharanidharan, R (International Journal of Engineering and Technology, 2017)
The security threats related to current IP configuration and also includes with Threshold Cryptography (TC). Circulated situations are attractive more prevalent as these knowledge such as networks, aim to enable a large scale collaboration for resource sharing outline in the network. Secure verification is the interesting concern for such surroundings. The proposed system to maintain a two stages for improving the network security based on IP addressing time in the network. An first stage is threshold cryptography and another one is Neighbor discovery protocol (NDP). In main objectives of our proposed work is Threshold Cryptography based addressing scheme in network, also the authorization process fully depends on Neighbor discovery protocol based frameworks. The goal of the Neighbor discovery protocol is to support a Mobile Node (MN) roaming across network fields without communication disturbance or recognizable delay. Moreover, this approach also ensures correct synchronization between nodes that send overlapping data on the network. Finally, using this NDP-TC during data transfer time packet loss is very low so the network security is automatically increased.Â